Phase I/II trial of autologous stem cell transplantation in systemic sclerosis: procedure related mortality and impact on skin disease. Issue 6 (1st June 2001) - Binks, M; Passweg, J R; Furst, D; McSweeney, P; Sullivan, K; Besenthal, C; Finke, J; Peter, H H; van Laar, J; Breedveld, F C; Fibbe, W E; Farge, D; et al.
Abstract : BACKGROUND: Systemic sclerosis (SSc, scleroderma) in either its diffuse or limited skin forms has a high mortality when vital organs are affected. No treatment has been shown to influence the outcome or significantly affect the skin score, though many forms of immunosuppression have been tried. Recent developments in haemopoietic stem cell transplantation (HSCT) have allowed the application of profound immunosuppression followed by HSCT, or rescue, to autoimmune diseases such as SSc. METHODS: Results for 41 patients included in continuing multicentre open phase I/II studies using HSCT in the treatment of poor prognosis SSc are reported. Thirty seven patients had a predominantly diffuse skin form of the disease and four the limited form, with some clinical overlap. Median age was 41 years with a 5:1 female to male ratio. The skin score was >50% of maximum in 20/33 (61%) patients, with some lung disease attributable to SSc in 28/37 (76%), the forced vital capacity being <70% of the predicted value in 18/36 (50%). Pulmonary hypertension was described in 7/37 (19%) patients and renal disease in 5/37 (14%). The Scl-70 antibody was positive in 18/32 (56%) and the anticentromere antibody in 10% of evaluable patients. Peripheral blood stem cell mobilisation was performed with cyclophosphamide or granulocyte colony stimulating factor, alone or in combination. Thirty eight patients had ex vivo CD34 stem cell selection, with additional T cell depletion in seven. Seven conditioning regimens were used, but six of these used haemoimmunoablative doses of cyclophosphamide +/- anti-thymocyte globulin +/- total body irradiation. The median duration of follow up was 12 months (3–55). RESULTS: An improvement in skin score of >25% after transplantation occurred in 20/29 (69%) evaluable patients, and deterioration in 2/29 (7%). Lung function did not change significantly after transplantation. One of five renal cases deteriorated but with no new occurrences of renal disease after HSCT, and the pulmonary hypertension did not progress in the evaluable cases. Disease progression was seen in 7/37 (19%) patients after HSCT with a median period of 67 (range 49–255) days. Eleven (27%) patients had died at census and seven (17%) deaths were considered to be related to the procedure (direct organ toxicity in four, haemorrhage in two, and infection/neutropenic fever in one). The cumulative probability of survival at one year was 73% (95% CI 58 to 88) by Kaplan-Meier analysis. CONCLUSION: Despite a higher procedure related mortality rate from HSCT in SSc compared with patients with breast cancer and non-Hodgkin's lymphoma, the marked impact on skin score, a surrogate marker of mortality, the trend towards stabilisation of lung involvement, and lack of other treatment alternatives justify further carefully designed studies. If future trials incorporate inclusion and exclusion criteria based on this preliminary experience, the predicted procedure related mortality should be around 10%.